Guide to the literature of the life sciences - Smith, Roger Cletus 1888- (Burgess Pub. Co., 1972)
Current guide to the use of the literature of biology and related areas. Arranged into chapters. Covers literature problems of the scientist, the library, bibliographies, abstract tools, bibliographic form, serials, taxonomic literature, and techniques of searching the literature and preparing a scientific paper. References included with chapters. General index. 1st ed., 1942; 7th ed., 1967.